KINETIC PARAMETERS OPTIMIZATION PROTEOLYTIC BACTERIA ISOLATED FROM CONTAMINATED MARINE ENVIRONMENTS - Arauco P., Katherine (2004)
lt was isolated a total of 124 strains marine bacteria. The obtained results gave 70 strains (56.44%) with proteolytic activity. Five strains that presented the best halos to determinative the optimization of kinetic parameters (NaCl, pH and temperature). The genus Pseudomonas presented the best proteolytic activity with extracts of 72 hours. The phenotypic characterization of five strains, were 3 of genus Aeromonas, one Pseudomonas and one Alcaligenes.